Both Radiofrequency Microtenotomy and Physical Therapy Provide Significant Improvements in Patients With Chronic Midportion Achilles Tendinopathy at a Minimum 5‐Year Follow‐Up - Hayat Jirde Ali; Khaled Meknas; Jüri‐Toomas Kartus; Dana Meknas (Arthroscopy, Sports Medicine, and Rehabilitation, 2026)
Purpose To evaluate a minimum 5‐year follow‐up of patients who were treated with either bipolar radiofrequency microtenotomy (RFM) or physical therapy (PT) for midportion Achilles tendinopathy between 2016 and 2018. Methods All subjects who participated in a previous randomized controlled trial (n = 38) between 2016 and 2018 were invited to fill out a questionnaire between January and July 2025 to evaluate the outcomes at a minimum of 5‐year follow‐up. Patients who had undergone further surgical treatment were excluded. Visual analog scale (VAS) for pain and Foot and Ankle Outcome Score (FAOS) were used to assess clinical outcomes. Results A total of 25 out of the 38 (66%) invited subjects were included: 13 (65%) in the RFM group and 12 (67%) in the PT group. Both treatment groups had significantly improved VAS at the minimum 5‐year follow‐up compared with preintervention. The RFM group improved from 7.3 ± 1.2 to 0.3 ± 0.8 ( P = .002), whereas the PT group improved from 5.7 ± 0.3 to 2.2 ± 2.6 ( P = .010). The RFM group had significantly better VAS than the PT group at the minimum 5‐year follow‐up ( P = .019). All parameters in the FAOS were significantly improved for patients in both the RFM group and the PT group. Quality of life was the only variable of the FAOS with significantly better results for RFM in comparison with PT ( P = .047). Conclusions In this study, patients with chronic midportion Achilles tendinopathy reported significant improvements in VAS and FAOS 6 to 9 years after intervention with either RFM or PT. The RFM group reported significantly better outcomes in VAS and quality of life. However, because of loss to follow‐up, the study is underpowered, and the results should be interpreted with caution. Level of Evidence Level II, therapeutic, poor‐quality randomized controlled trial (